Kementerian Sumber Manusia - Othman, Muhammad Hilmi; Mat Zizan, Muhammad Thaqif; Abu Hassan Shaari, Muhammad Helmi; Muhammad Fauzri, Muhammad Fareez (2024)
This Integrated Final Project is an extensive exploration of the diverse aspects of the building industry, encompassing organizational management, technology, design, property, building economics and finance, law, communication, and project planning and management. As a crucial element of the Diploma program, it integrates all the courses studied, offering students exposure to current industry processes and practices. This equips them with the necessary knowledge and skills to adeptly handle real-world situations in the building sector. The methodological approach of this project involved an onsite visit to the Kementerian Sumber Manusia building. This direct engagement provided an invaluable opportunity for students to learn beyond the theoretical framework, gaining practical insights and firsthand experience in a real-world setting. A key finding from this field experience was the assessment of the Kementerian Sumber Manusia building’s condition, which was found to be in a commendable state. This hands-on evaluation was pivotal in understanding the practical aspects of building assessment and maintenance, offering a tangible context to the theoretical knowledge acquired. The project culminated in the development of essential skills for compiling a thorough and professional report on the Kementerian Sumber Manusia building. This aspect of the project not only solidified the theoretical knowledge imparted throughout the Diploma program but also provided a practical framework for real-world building analysis and reporting. The ability to produce detailed, industry-standard reports, as demonstrated in this project, signifies the readiness of the students to tackle the challenges in the building industry, particularly in areas of assessment and maintenance.